The Role and Position of the Notary Deed in the Conviction of the Defendant - Aditya Fauzi Indarto; Mujiono Hafidh Prasetyo (Law Development Journal, 2023)
This study aims to determine the role and position of an authentic deed in the form of a peace agreement between the parties referring to the case study of Decision Number 69/Pid.B/2022/PN Smg. The research method used is a normative juridical approach (library research), which examines existing legal problems by linking laws and regulations, books, official documents, publications, and research results, which are discussed using secondary data which includes principles, norms, rules, and laws and regulations in accordance with the research. The result of this research is that an authentic deed in the form of a peace agreement between the parties in a criminal case can be used as the main consideration in mitigating the defendant. The peace agreement in verdict number 69/Pid. B/2022/PN Smg implemented by the parties is a manifestation or implication of ADR which has fulfilled the elements of out-of-court case settlement / Afdoening Buiten process. In this discussion, the public prosecutor and judge in decision number 69/Pid.B/2022/PN Smg were very concerned about the existence of a peace agreement between the parties (perpetrator and victim). This is evidenced by the lenient charges from the Public Prosecutor against the defendant in the form of a conditional sentence, namely imprisonment for 5 (five) months with a probationary period of 10 (ten months). The judge in his decision also handed down a lenient sentence against the defendant, namely imprisonment for 5 (five) months with a probationary period of 10 (ten months) or the same as the charges of the public prosecutor.